Utilization of Robotic Exoskeleton for Overground Walking in Acute and Chronic Stroke - Nolan, Karen J.; Karunakaran, Kiran K.; Roberts, Pamela; Tefertiller, Candy; Walter, Amber M.; Zhang, Jun; Leslie, Donald; Jayaraman, Arun; Francisco, Gerard E. (Frontiers in Neurorobotics, 2021)
Stroke commonly results in gait deficits which impacts functional ambulation and quality of life. Robotic exoskeletons (RE) for overground walking are devices that are programmable to provide high dose and movement-impairment specific assistance thus offering new rehabilitation possibilities for recovery progression in individuals post stroke. The purpose of this investigation is to present preliminary utilization data in individuals with acute and chronic stroke after walking overground with an RE. Secondary analysis on a subset of individuals is presented to understand the mechanistic changes due to RE overground walking. Thirty-eight participants with hemiplegia secondary to stroke were enrolled in a clinical trial conducted at eight rehabilitation centers. Data is presented for four sessions of overground walking in the RE over the course of two weeks. Participants continued their standard of care if they had any ongoing therapy at the time of study enrollment. Gait speed during the 10 Meter Walk Test, Gait deviations and the Functional Ambulation Category (FAC) data were collected before (baseline) and after (follow-up) following the RE walking sessions. Walking speed significantly increased between baseline and follow-up for participants in the chronic (p<0.01) and acute (p<0.05) stage of stroke recovery. FAC level significantly improved (p<0.05) and there were significantly fewer (p<0.05) gait deviations observed for participants in the acute stages of stroke recovery between baseline and follow-up. Secondary analysis on a subset of eight participants indicated that after four sessions of overground walking with the RE, the participants significantly improved their spatial symmetry. The walk time, step count and ratio of walk time to up time increased from first session to the last session for participants in the chronic and acute stages of stroke. The RE was effectively utilized for overground walking for individuals with acute and chronic stroke with varying severity levels. The results demonstrated an increase in walking speed, improvement in FAC and a decrease in gait deviations (from baseline to follow-up) after four sessions of overground walking in the RE for participants. In addition, preliminary data indicated that spatial symmetry and step length also improved after utilization of an RE for overground walking.